2021
DOI: 10.1136/bmjnph-2020-000209
|View full text |Cite
|
Sign up to set email alerts
|

Potential for elimination of folate and vitamin B12deficiency in India using vitamin-fortified tea: a preliminary study

Abstract: IntroductionThe majority of Indian women have a poor dietary folate and vitamin B12 intake resulting in their chronically low vitamin status, which contributes to anaemia and the high incidence of folate-responsive neural-tube defects (NTDs) in India. Although many countries have successfully deployed centrally-processed folate-fortified flour for prevention of NTDs, inherent logistical problems preclude widespread implementation of this strategy in India. Because tea—the second most common beverage worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…We had confirmed that nearly all 60 young women (who were nursing students at a college in Sangli, India) had low-folate status and nearly two-thirds had a low-Vitamin-B 12 status, similar to that of women in the nearby city of Pune. [ 26 ] Accordingly, in another group of 43 young Indian women (nursing and homeopathy students in Sangli) with borderline or low-vitamin stores,[ 26 ] we determined if consumption of a single daily cup of tea prepared from teabags that were individually fortified with both these water-soluble vitamins could lead to a rise in serum folate and Vitamin B 12 within 2 months. The “experimental group” was divided into two subgroups to receive tea from teabags fortified with two strengths of vitamins: 1-mg folate plus either 0.1-mg or 0.5-mg Vitamin B 12 per teabag (containing 2 g of tea); one teabag was used per cup of tea.…”
Section: T Ea – a U Niquely I ...mentioning
confidence: 99%
See 3 more Smart Citations
“…We had confirmed that nearly all 60 young women (who were nursing students at a college in Sangli, India) had low-folate status and nearly two-thirds had a low-Vitamin-B 12 status, similar to that of women in the nearby city of Pune. [ 26 ] Accordingly, in another group of 43 young Indian women (nursing and homeopathy students in Sangli) with borderline or low-vitamin stores,[ 26 ] we determined if consumption of a single daily cup of tea prepared from teabags that were individually fortified with both these water-soluble vitamins could lead to a rise in serum folate and Vitamin B 12 within 2 months. The “experimental group” was divided into two subgroups to receive tea from teabags fortified with two strengths of vitamins: 1-mg folate plus either 0.1-mg or 0.5-mg Vitamin B 12 per teabag (containing 2 g of tea); one teabag was used per cup of tea.…”
Section: T Ea – a U Niquely I ...mentioning
confidence: 99%
“…We subsequently documented that daily use of vitamin-fortified tea for 2 months led to significant rises in their serum folate and Vitamin-B 12 levels, and hemoglobin concentration, which signified a clinical response; by contrast, there were insignificant changes in women using daily unfortified tea. [ 26 ]…”
Section: T Ea – a U Niquely I ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a study directed at isolating strains of lactobacilli synthesizing the highest folate concentration by milk fermentation, it was found that Lactobacillus fermentum (from kefir granules), Lactobacillus plantarum (from salted mustard), and Lactobacillus rhamnosus (from breast milk) produced the highest concentrations of folic acid in the absence of pre-existing folate in milk [33]. An interventional study conducted in India to estimate the potentiality of tea as a scalable vehicle for fortification with vitamins B9 and B12 successfully showed that the daily consumption of a cup of vitamin-fortified tea for two months could benefit women of reproductive age [34]. Investigations on the dietary value of freshwater living green unicellular algae Chlorella species proved the presence of large amounts of folate.…”
Section: Sourcesmentioning
confidence: 99%